Premature Rupture of Membrane Outcome Determinants in Reproductive Age Women - Zakirah, Sarah Chairani; Eyanoer, Putri Chairani; Azali, Chairul Nurdin; Wiweko, Budi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: